2005
DOI: 10.1097/01.sap.0000146860.48187.d7
|View full text |Cite
|
Sign up to set email alerts
|

Salvage of Infected Cartilage Grafts for Nasal Reconstruction With a Through-and-Through Irrigation System

Abstract: Development of a wound infection after nasal reconstruction can place the entire reconstructive effort in jeopardy. The approach to management in these cases has traditionally entailed wound drainage, removal of involved graft material, and debridement of nonvital tissue. Following adequate wound healing, delayed reconstruction is then performed, with the final result often compromised in form and function. We present a case of a postoperative wound infection following reconstruction of a traumatic nasal defor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Delgado-Lopez et al [11] and Auguste and McDermott [12] succeeded in preserving a previous bone flap using an antibiotic irrigation system. This effective indwelling antibiotic irrigation system has also been shown to be useful for salvaging infected nasal cartilage, in addition to cranial bone flaps [13]. Our case differs from previous reports in which the prosthetic cranial implant was successfully salvaged with an antibiotic irrigation system along with scalp defect reconstruction.…”
Section: Discussionmentioning
confidence: 53%
“…Delgado-Lopez et al [11] and Auguste and McDermott [12] succeeded in preserving a previous bone flap using an antibiotic irrigation system. This effective indwelling antibiotic irrigation system has also been shown to be useful for salvaging infected nasal cartilage, in addition to cranial bone flaps [13]. Our case differs from previous reports in which the prosthetic cranial implant was successfully salvaged with an antibiotic irrigation system along with scalp defect reconstruction.…”
Section: Discussionmentioning
confidence: 53%
“…According to the authors, a 3-year follow-up demonstrated no recurrence of the nasal infection with complete maintenance of the immediate postoperative shape, function, and aesthetics. 10 The through-and-through apparatus described in the 2 case reports are similar, as is the 7-day period of use with intravenous antibiotics. However, there are major differences (aside from the ages of the patients and the anatomic locations of the costochondral constructs), most notably between the concentrations and types of antibiotics employed (1 mg/1 mL H 2 O of gentamicin sulfate vs a combination of 50,000 U/L of bacitracin and 80 mg/L of gentamicin), the rates of continuous irrigation (5 mL per hour vs 50 mL per hour), and the type of drainage (free gravity vs closed suction).…”
Section: Discussionmentioning
confidence: 97%
“…Washing the exposed portions of the infected cartilage grafts with culture-specific antibiotics has proven effective in the treatment of chondritis of the ear. 9,10 The successful salvage of an infected cartilage graft for nasal reconstruction utilizing a through-and-through irrigation system has been reported in the literature. 10 In the nasal reconstruction salvage case, a 60-year-old patient presented 1 month after a nasal reconstruction with an abscess that lay in direct continuity with the recently placed cartilage spreader grafts, the dorsal onlay graft, and the nasal tip grafts.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Acute or late infection in nasal reconstruction usually leads to cartilage loss, soft-tissue collapse, and poor result. 1 …”
mentioning
confidence: 99%